2018
DOI: 10.1155/2018/8909714
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Vessel Density Reversal after Trabeculectomy in Glaucoma

Abstract: Purpose To evaluate the microvascular changes at the peripapillary area and optic disc in glaucomatous eyes after IOP lowering by trabeculectomy using OCT angiography. Methods 25 patients with primary open-angle glaucoma (POAG) who underwent trabeculectomy by a single surgeon were evaluated. Using optical coherence tomography angiography, vessel density was evaluated within the whole image, peripapillary, nasal region, and temporal region. Peripapillary vessel density was measured preoperative, 1 week, 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 33 publications
(31 reference statements)
2
41
3
1
Order By: Relevance
“…Generalizability may be limited due to the small sample size, predominantly Caucasian population, and exclusion of eyes with high myopia, tilted discs, or previous glaucoma surgeries, which may affect OCTA measurements. 64 Retinal microvasculature can be negatively affected by aging, 65 yet we observed decreased ONH and peripapillary vessel density in patients with POAG, who were younger than controls. Although we tried to address the age difference during recruiting, we ultimately adjusted for age in multivariable analyses.…”
Section: Discussionmentioning
confidence: 64%
“…Generalizability may be limited due to the small sample size, predominantly Caucasian population, and exclusion of eyes with high myopia, tilted discs, or previous glaucoma surgeries, which may affect OCTA measurements. 64 Retinal microvasculature can be negatively affected by aging, 65 yet we observed decreased ONH and peripapillary vessel density in patients with POAG, who were younger than controls. Although we tried to address the age difference during recruiting, we ultimately adjusted for age in multivariable analyses.…”
Section: Discussionmentioning
confidence: 64%
“…From an initial selection of 4516 studies, ten 14,21,[28][29][30][31][32][33][34][35] were included in the systematic review (Figure 1). A Kappa agreement of 0.81 was obtained for the eligibility of the full-texts (good agreement).…”
Section: Study Selectionmentioning
confidence: 99%
“…The included studies had follow-up periods between 3 months 30,31,35 and 2.6 years. 21 There was a wide variation in the reported VD values, in the slab/retinal depth assessed, in the selection criteria, and the OCTA devices used.…”
Section: Figurementioning
confidence: 99%
“…Our study aimed to investigate the potential effect of Tafluprost on flow density in POAG patients using OCT-A examination of both the optic nerve head and the macular region in a cross-sectional approach. Hee In et al demonstrated that lowering the IOP could lead to an increased flow density correlated to the IOP reduction [43]. Therefore, an interventional approach to evaluate the effect of Tafluprost on flow density could be confounded by its IOP-lowering properties.…”
Section: Discussionmentioning
confidence: 99%